2018
DOI: 10.1186/s12876-018-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell transplantation improves chronic colitis-associated complications through inhibiting the activity of toll-like receptor-4 in mice

Abstract: BackgroundA variety of extra-intestinal manifestations (EIMs), including hepatobiliary complications, are associated with inflammatory bowel disease (IBD). Mesenchymal stem cells (MSCs) have been shown to play a potential role in the therapy of IBD. This study was designed to investigate the effect and mechanism of MSCs on chronic colitis-associated hepatobiliary complications using mouse chronic colitis models induced by dextran sulfate sodium (DSS).MethodsDSS-induced mouse chronic colitis models were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…MSC are considered as a potential therapy for IBD and other autoimmune diseases [ 26 ]. Previously, our study found that injection of stem cells can improve colitis and its associated complications in mice [ 27 ]. Accumulating studies also revealed that the effects of anti-inflammatory and immunosuppression were mainly contributed by exosome secretion [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSC are considered as a potential therapy for IBD and other autoimmune diseases [ 26 ]. Previously, our study found that injection of stem cells can improve colitis and its associated complications in mice [ 27 ]. Accumulating studies also revealed that the effects of anti-inflammatory and immunosuppression were mainly contributed by exosome secretion [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, these effects depend, to a large extent, on the time and concentration of the administered MSCs [39]. Upon transplantation, MSCs can inhibit the intestinal endotoxemia and liver inflammation via the LPS/TLR4 pathway, and improve chronic colitis-related hepatobiliary complications [40].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 activates the endotoxin-induced innate immune system and the NF-κB pathway, further stimulating the expression of pro-inflammatory factors (45). MSCs reduce the level of TLR4, leading to the reduction of pro-inflammatory factors and alleviating intestinal inflammatory response (46). A previous study has demonstrated that MSCs inhibited the proliferation and activation of cluster of differentiation (CD)4 + T cells and the differentiation of CD4+ T cells into Th1 and Th17 cells (47).…”
Section: Discussionmentioning
confidence: 99%